Impact of Digital Media Usage on Preventive Behavior among Young Adults - Freeman, Karen Sabina; Chan, Pee Ven; Revathi, Sagadavan (INTI International University, 2022)
Most countries have endorsed preventive behavioral guidelines or SOPs to reduce the spread of the COVID-19 virus like using facemasks and maintaining physical distancing. Nevertheless, there are studies indicating that young adults least adhere to such guidelines which pose a public health concern. This study sought to establish the top digital media used by young adults in Malaysia, the reasons for those choices, and to assess the relationship between digital media usage and preventive behaviors. Results from an online survey (N=389) revealed that WhatsApp is most consumed by young adults and the main reason for accessing digital media is to get immediate/fast, up-to-date news and information. In addition, results revealed that TikTok has the highest mean of preventive behavior among young adults. Findings from this study establish that users consume specific digital media for discrete reasons. Results also reveal that the top most preventive behavior recorded by TikTok users is wearing face masks. These have implications for relevant policy makers to prepare for future contagious outbreaks.